ANGKA LEMPENG TOTAL PLATE COUNT PADA BEBERAPA UNIT PENGOLAHAN IKAN ASAP PINEKUHE DI KABUPATEN SANGIHE - ELY KARIMELA; Jeffri Anthonius Mandeno (Jurnal Ilmiah Tindalung, 2019)
Salah satu produk hasil olahan perikanan asap yang dimiliki oleh nelayan Kabupaten Kepulauan Sangihe adalah Pinekuhe. Penelitian ini bertujuan untuk mengetahui tingkat pencemaran mikroba pada ikan asap Pinekuhe hasil olahan nelayan Kabupaten Kepulauan Sangihe. Pengamatan kemunduran mutu produk ikan asap Pinekuhe, diamati melalui uji total plate count. Hasil penelitian menunjukkan nilai total plate count pada pengolah A, B, C dan D, berturut-turut sebesar 1,3 x 104 CFU/g. 2,6 x 104 CFU/g, 6,9 x 104 dan 1,2 x 104 CFU/g. Jumlah total bakteri pada pengolah A, B, C dan D memenuhi syarat sesuai Standar Nasional Indonesia mengenai batas cemaran mikroba pada ikan asap. It is one of the resulted products which are prepared by the smoke fisheries owned by the fisherman in Regency of the Sangihe Island known as Pinekuhe. The aim of the research is to know the higher contamination of microbe on the smoke fish Pinekuhe. It was the product prepared by the fisherman in the Regency of the Sangihe Island. Observation of the deterioration of the quality of Pinekuhe smoked fish products was observed through a total plate count test. The results showed the total plate count values in processors A, B, C and D, respectively 1.3 x 104 CFU / g. 2.6 x 104 CFU / g, 6.9 x 104 and 1.2 x 104 CFU / g. The total number of bacteria in processors A, B, C and D meet the requirements according to the Indonesian National Standard regarding the limits of microbial contamination in smoked fish.